Vesicocervical fistula following vesicovaginal fistula repair report - Rahman, Hamudur; Islam, Md. Saiful; lslam, Rafiqul; Khairuzzaman, Md.; Hasan, Sajid (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Vesicocervical fistula following vesicovaginal fistula repair is a very rare condition. It is a complication following repeated lower uterine cesarean section. We report a case of an young married woman who was admitted in the department of urology, Banghabandhu Sheikh Mujib Medical University Hospital with vesico-cervical fistula following vesicovaginal fistula repair. Reposition of cervix into vaginal vault and repair of urinary bladder was done. There was no such report of vesicocervical fistula following vesicovaginal fistula repair from Bangladesh.